Risk and returns of Indian listed firms after demonetisation - Varsha Sureshkumar; P. Balasubramanian (Cogent Economics & Finance, 2021)
This paper aims to understand the impact of demonetisation on the returns of listed firms in the NSE, as well as changes to their corresponding industry level systematic risk. Firstly, this paper examined a larger sample of Indian listed firms and a broader group of industries in its analysis compared to prior studies. Secondly, the changes to systematic risk due to demonetisation across industries with listed firms was measured. The study uses event study methodology over a thirteen-day event window (six days before and six days after the announcement) to test for abnormal returns across 1,054 listed firms. A regression analysis of 57 industry level returns is performed to test for changes in systematic risk. Significant negative abnormal returns are found for over 100 firms and 12 out of the 57 industry divisions in the sample. The same group of industries also show an increase in their systematic risk in the short run. This indicates that parts of the formal economy were also seriously affected by demonetisation. However, our paper does not find any long-term effect due to demonetisation.
Keywords: G12; G14; G18; 330; abnormal returns; demonetisation; event study; listed firms; money supply shock; systematic risk